Green Roofs in Urban Landscapes - Eva Worden; Diana Guidry; Annabel Alonso Ng; Alex Schore (EDIS, 2004)
Growing apace with urban populations is the dilemma of how to create and sustain a healthy urban ecosystem. Cities increasingly struggle to cope with the urban heat island effect, stormwater runoff, altered weather patterns, air pollution, loss of tree canopy and greenspace, noise, and loss of wildlife habitat. Green roofs, which are specially designed landscapes atop buildings, can provide solutions to many of these problems as well as enhance the quality of life for urban residents. This document is ENH 984, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date September 2004.